Factors Affecting Farmers’ Participation in Contract Farming: The Case of Broiler Sector in Indonesia - M. Rondhi; J. M. M. Aji; A. F. Hasan; R. Yanuarti (Tropical Animal Science Journal, 2020)
Contract farming (CF) has been used extensively to integrate broiler value chain both in the developed and developing countries. Participation in CF is associated with the increased farm productivity and farmer income. Therefore, the purpose of this study was to analyze factors affecting Indonesian broiler farmers’ participation in CF. This study used the nationally-representative data of smallholder broiler farmers in Indonesia. The data were the results of the 2014 Indonesian Livestock Farm Household Survey (ILFHS) and consisted of 1,142 farmers distributed in 20 provinces. Logistic regression was used to analyze thirteen factors that potentially affected farmers’ decision to participate in CF. Those factors were age, gender, education, household size, farming experience, farm area, broiler population, cooperative membership, cooperative service, farmer group membership, farmer group service, farmer association, and agricultural extension. The results showed that six factors had statistically significant effects on farmers' decision to participate in CF. Education, land size, population, farmer group, and agricultural extension have a positive influence on farmers' decisions. Meanwhile, cooperative service has a negative effect. Farmer group and agricultural extension service have the strongest effect on participation in CF. The results suggest that farmer groups and extension services to small scale farmers are promising to improve their participation in CF.